The legal status of a minor in criminal proceedings (Journal of actual problems of jurisprudence, 2018)
The problem of criminal juvenile justice. This is due to the fact that the increase in the current conditions of the educational function of minors, due to the requirements that arise from government decisions and focused on education of the younger generation. The reasons for this include the need for mainstreaming should be an increase in efforts by the judiciary to properly perform all the tasks of the justice of the juvenile of this age category.Key words: minor, trial, justice, criminal procedure, evidence.